Acute respiratory infections and its associated risk factors among children aged 6–59 months in Ghana: a multinomial regression analysis of the 2022 demographic and health survey - Klu, Desmond; Alhassan, Amidu; Dansu, Charity Akpene (Frontiers in Public Health, 2025)
BackgroundAcute Respiratory Infections (ARIs) remain a critical health concern, particularly among children aged 6–59 months, where they are among the leading causes of morbidity and mortality worldwide. Globally, ARIs significantly contribute to child mortality, accounting for nearly 15% of all deaths in children under 5 years of age.ObjectiveTo assess the risk factors associated with ARI severity among children aged 6–59 months in Ghana.Research designThis study utilized data from the 2022 Ghana Demographic and Health Survey (GDHS), focusing on a weighted sample of 541 children aged 6–59 months who exhibited symptoms of ARI. Multinomial logistic regression analyses were conducted to examine maternal, household, and child-related predictors of ARI. A significant p-value was set at 0.05.ResultsThe prevalence of ARI was 17.1% for chest problems only, 66.1% for nose breathing difficulties, and 16.8% for both nose and chest problems. Key predictors of ARI included coastal zone residency (aOR = 7.89; CI: 2.26–27.60), maternal illiteracy (aOR = 0.34; CI: 0.12–0.93), maternal ethnicity (Akan: aOR = 0.12; CI: 0.02–0.85), and age of household head (20–29 years: aOR = 59.08; CI: 3.04–1,150.14). Boys were more likely than girls to experience both nose and chest problems (aOR = 3.44; CI: 1.61–7.34), and younger children, particularly those under 12 months, were at higher risk of ARI (aOR = 21.04; CI: 3.34–132.64). Children who were not breastfeeding (aOR = 2.62; CI: 1.15–5.94) and had not suffer from diarrhea (aOR = 2.28; CI: 1.19–4.38) were more at risk of ARI.ConclusionThe findings highlight the significant role of maternal education, household sanitation, and child-specific factors in influencing ARI risk among children in Ghana. Efforts to improve maternal education, enhance sanitation facilities, and implement targeted interventions for high-risk children are critical to reducing the burden of ARI in Ghana.